LIFELONG LEARNING: NEW PARADIGMS AND SUSTAINABLE PERSPECTIVES - Rasulova, Durdona Bakhronovna (FAN, TA'LIM VA AMALIYOT INTEGRATSIYASI, 2022)
In this article, the author deals with the importance of the concept of "lifelong learning", highlighting life situations and the culture of education and employment, creating a comparative and causal analysis of the theory of lifelong learning. The author also gives possible ways of developing this direction and the results we will encounter in the future.